Factors influencing the utilisation of facility-based delivery in Nigeria: a qualitative evidence synthesis - Suleiman E Mshelia; Chukwudi V Analo; Andrew Booth (Journal of Global Health Reports)
# Introduction High-quality facility-based birth reduces maternal and perinatal morbidity and mortality. Previous multi-country systematic reviews have analysed qualitative research studies to understand the barriers and facilitators of delivery in a health facility. However, questions remain as to the extent to which generic multi-context reviews capture nuanced insights from a specific country context. Nigeria contributes significantly to the global burden of maternal mortality and hence the need to explore the country’s contextual factors affecting maternal mortality viz-a-viz a previous international review.